Accuracy of the cm carbide method when testing counter-floors used in the construction industry - Trochonowicz, Maciej; Szostak, Bartosz; Lackorzyński, Marek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Special requirements are placed on finishing materials and foundations for these materials. The technical datasheets for wooden floors contain detailed moisture guidelines regarding counter-floors for these materials. To check the moisture level, the carbide method (CM method) is recommended by manufacturers and many specialists. The authors of the paper performed moisture tests for various counter-floors (anhydrite and cement jointless floors, cement-sand mixtures) using the direct gravimetric (laboratory) method and the carbide method. Test results were collected and analyzed.
Keywords: wooden floor; moisture; CM method; carbide method; counter-floor; jointless floor; podłoga drewniana; wilgotność; test wilgotności; metoda CM